A Wavelet-Based Approach with NLMS Equalization and Fading Channel Compensation for Improved Spectral Efficiency and Error Rate - J, Harilal; K, Kalpana; Shirisha, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Within the realm of communication, Orthogonal Frequency Division Multiplexing (OFDM) has emerged as a highly effective and commendable approach. The fundamental structure of Orthogonal Frequency Division Multiplexing (OFDM) encompasses the utilization of Fast Fourier Transform (FFT) to efficiently compute the Discrete Fourier Transform (DFT) of a given source signal through expedited computational processes. Nevertheless, the Orthogonal Frequency Division Multiplexing (OFDM) system utilizing Fast Fourier Transform (FFT) encounters various limitations, such as inadequate localization, increased error rates at high data rates, and limited spectrum efficiency. In order to tackle these issues, the utilization of wavelet-based orthogonal frequency division multiplexing (OFDM) emerged as an alternative to substitute the fast Fourier transform (FFT) with the discrete wavelet transform (DWT). In this study, we have designed an upgraded discrete wavelet transform-orthogonal frequency division multiplexing (DWT-OFDM) system using normalized least mean squares (NLMS) equalization approach. The objective of this implementation is to minimize the bit error rate (BER) values in comparison to the conventional fast Fourier transform-orthogonal frequency division multiplexing (FFT-OFDM) system. Furthermore, a channel equalization technique is also suggested for fading environments, such as Rayleigh, Rician, and additive white Gaussian noise (AWGN) circumstances. Additionally, the BER comparison also includes various modulation levels, which reveal the effectiveness of the proposed system compared to the typical FFT-OFDM method.